Analisis Perhitungan Kebutuhan Tenaga Kerja Petugas Riset Rekam Medis Pusat Berdasarkan Teori WISN di RSUPN Dr. Cipto Mangunkusumo - Putri Alipiyah Nurazmi; Atma Deharja; Jalahan Pandeangan (J-REMI : Jurnal Rekam Medik dan Informasi Kesehatan, 2020)
National Center General Hospital Dr. Cipto Mangunkusumo functions as an educational hospital, so the medical record file is often used for research materials. It can be seen from the hospital data in 2019 that there were 53,963 requests for medical record files, but only 42,138 medical record files could be fulfilled by research officers, meaning that 22% of files could not be provided by research officers. If this is done continuously, it will cause a decrease in the quality of the research officer. Based on observations that have been made on 2 people from the Medical Records Research Center Dr. Cipto Mangunkusumo is known that the officer concurrently had several jobs. This causes the workload that is not in accordance with the number of officers. The purpose of this study was to analyze the workforce needs of the Central Medical Records research staff based on WISN theory at Dr. RSUPN. Cipto Mangunkusumo. This type of research uses qualitative research with 2 informants. Data collection methods are observation, interviews, and documentation. Based on the workload calculation using the WISN method, it is known that the number of workers needed in the research unit is 8 people. It is expected that with the results of the calculation of labor needs based on WISN theory can be used as an effort to plan the addition of officers to improve the quality of hospital services and in accordance with the existing workload.